(untitled) (Journal of Mechanical Engineering, 2017)
Non-revenue Water (NRW) is an important component of commercial water system management. NRW is the result of pipelines leakage, improper, illegal service connections and theft water. NRW contributes system loss that is a buzzword. Actually, NRW is uncounted water that has been produced but it is confirmed to be lost before it consumes the customer. This matter agitates for all concern and specially it affects the whole economy. Dhaka Water Supply and Sewerage Authority (DWASA) is one of the main utilities in Dhaka City and it is the most important sector of the Government of Bangladesh. The potable water distribution network has been installed at the whole area of the city and it covers periphery of the city and its extension is going from N. Gonj to Tongi as well as surrounding area of this city. Non-revenue water surveys were conducted on specific fields and areas that were selected randomly. It would be gradually becoming a serious issue affecting the interest of all concerned and would be one of the major crises to be solved with techno-managerial concept.